VAT pass-through: the case of a large and permanent reduction in the market for menstrual hygiene products - Alisa Frey; Justus Haucap (International Tax and Public Finance, 2023)
This paper examines the price effects of a VAT (value-added tax) reduction for menstrual hygiene products in Germany. Several aspects make this VAT reduction particularly interesting: the reduction is exogenous to economic conditions, the reduction was substantial and permanent, and demand can be assumed to be inelastic. We find that the VAT reduction was completely passed through to consumers. In fact, pass-through rates of significantly more than 100% can be observed. We find that the excess pass-through occurred in relatively competitive market segments, and that it is almost fully explained by retailers rounding down prices after the reduction.
Keywords: H22; H25; H32; K34; L81; 340; VAT; Pass-through; Hygiene products; Retail competition; Gender equality; Rounding effects; Tampon tax